1996
DOI: 10.1002/art.1780391018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of synovial tissue and synovial fluid as the source of nucleic acids for detection of Chlamydia trachomatis by polymerase chain reaction

Abstract: Objective. Difficulties in detecting Chlamydia trachomatis in human joints by polymerase chain reaction (PCR) may be related to whether synovial tissue or synovial fluid (SF) is used as the source of DNA in PCR amplification. In this study, a new PCR assay was developed and used to compare chlamydial DNA in paired samples of SF and synovial tissue from patients with arthritis.Methods. The PCR assay targeted the ribosomal RNA operons, which are present in 2 copies on the C trachomatis chromosome. DNA from sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
63
0
6

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 26 publications
4
63
0
6
Order By: Relevance
“…A study published in 2009 reported that C. trachomatis DNA in ReA and uSpA patients is rather high (100% and 64%, respectively) [13], while other studies reported relatively low frequencies (25%) [11]. Thus, published data on the use of PCR for the detection of intraarticular C. trachomatis varies greatly in patients with ReA and uSpA [10,33]. Since no results are available on inter-laboratory variability, these differences cannot be simply attributed to varying prevalence, as they may reflect different sensitivities and specificities of the employed PCR.…”
Section: Discussionmentioning
confidence: 99%
“…A study published in 2009 reported that C. trachomatis DNA in ReA and uSpA patients is rather high (100% and 64%, respectively) [13], while other studies reported relatively low frequencies (25%) [11]. Thus, published data on the use of PCR for the detection of intraarticular C. trachomatis varies greatly in patients with ReA and uSpA [10,33]. Since no results are available on inter-laboratory variability, these differences cannot be simply attributed to varying prevalence, as they may reflect different sensitivities and specificities of the employed PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the gene sequence for 16S rRNA, Bas et al (26) detected a major outer membrane protein (MOMP) gene sequence and 2 chlamydial plasmid sequences. Several investigators then reported obtaining positive PCR results for 16S rRNA (27,28). Gerard et al (29) took synovial specimens that tested positive for 16S rRNA by PCR and then further identified chlamydial gene products (glyQS, r-protein S5 and L5, and Hsp60) within a majority of these biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In such a case, it has been shown that Chlamydia trachomatis is the triggering pathogen for the arthritis in ϳ50% of patients (18,21,22), resulting in a pretest probability for Chlamydia-induced arthritis of 50%. The pretest probability for Chlamydia-induced arthritis in patients presenting with a clinical picture compatible with ReA but without a symptomatic preceding infection has been estimated at ϳ12% (18) and 22% (3) if the calculation is based on serologic findings or detection of Chlamydia in the urogenital tract, and at ϳ30% (23)(24)(25) if based on polymerase chain reaction (PCR) methods to look for Chlamydia trachomatis in synovial fluid. Therefore, calculations are made for the different pretest probabilities of 12% and 30%.…”
Section: Bacteria Triggering Reamentioning
confidence: 99%
“…Only small amounts of synovial fluid or membrane are necessary for such a test. In patients with undifferentiated arthritis but with a joint pattern compatible with ReA, chlamydial DNA has been detected by PCR in ϳ30% of cases in different countries (23)(24)(25). However, chlamydial DNA was also found in control groups such as patients with rheumatoid arthritis (25) or healthy subjects (30).…”
Section: Bacteria Triggering Reamentioning
confidence: 99%